MANAJEMEN KEUANGAN UNTUK UMKM - Maghfiroh, Siti (Jurnal Pengabdian Bisnis dan Akuntansi, 2023)
MSMEs are the main pillars (soko guru) of the Indonesian economy, the success of MSMEs is expected to improve the Indonesian economy as a whole. The success of MSMEs in running their business cannot be separated from the ability of MSMEs to manage funds. Good fund management will be very useful in making MSME decisions. One form of information that is useful in the decision making process by the owner or manager is accounting information (bookkeeping). MSME accounting is an information system that identifies, organizes and communicates MSME economic information. Economic information is useful for decision making. Financial reports are a process of transactions, recording processes and ultimately become financial reports. Financial reports consist of: balance sheet, profit and loss report and notes to financial reports.